2020
DOI: 10.1038/s41598-020-71931-w
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature-dependent microRNA expression analysis in rats: rno-miR-374-5p regulates apoptosis in skeletal muscle cells via Mex3B under hypothermia

Abstract: Forensic diagnosis of fatal hypothermia is considered difficult because there are no specific findings. Accordingly, exploration of novel fatal hypothermia-specific findings is important. To elucidate the molecular mechanism of homeostasis in hypothermia and identify novel molecular markers to inform the diagnosis of fatal hypothermia, we focused on microRNA expression in skeletal muscle, which plays a role in cold-induced thermogenesis in mammals. We generated rat models of mild, moderate, and severe hypother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Additionally, to explore the linkage among these 12 mutated genes, we utilized the KEGG database to examine the signaling pathways in which these genes are located. We found that several of the mutant genes are implicated in numerous important signaling pathways, both upstream and downstream, including the PI3K-AKT, MAPK, Ras, and JAK-STAT signaling pathways ( Christov et al, 2011 ; Hernandez-Varas et al, 2011 ; Clinkenbeard et al, 2016 ; Wang et al, 2017 ; Luo et al, 2018 ; Wang et al, 2018 ; Wu et al, 2019 ; Zhang et al, 2019 ; Chang et al, 2020 ; Schafer et al, 2020 ; Umehara et al, 2020 ; Ho and Bergwitz, 2021 ) ( Figure 5 ). These signaling pathways are involved in the regulation of cancer-related phenotypes, including cell cycle progression, cell survival, cell migration, signal transduction, and more.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to explore the linkage among these 12 mutated genes, we utilized the KEGG database to examine the signaling pathways in which these genes are located. We found that several of the mutant genes are implicated in numerous important signaling pathways, both upstream and downstream, including the PI3K-AKT, MAPK, Ras, and JAK-STAT signaling pathways ( Christov et al, 2011 ; Hernandez-Varas et al, 2011 ; Clinkenbeard et al, 2016 ; Wang et al, 2017 ; Luo et al, 2018 ; Wang et al, 2018 ; Wu et al, 2019 ; Zhang et al, 2019 ; Chang et al, 2020 ; Schafer et al, 2020 ; Umehara et al, 2020 ; Ho and Bergwitz, 2021 ) ( Figure 5 ). These signaling pathways are involved in the regulation of cancer-related phenotypes, including cell cycle progression, cell survival, cell migration, signal transduction, and more.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the precursor mRNA shearing and RNA processing and is associated with the action of cell cycle protein-dependent kinases ( 46 ). Additionally, CCNL1 may contribute to cell survival during cellular stress, such as cold stimulation ( 47 ). CCNT2 is a cyclin involved in the cell cycle and RNA transcription ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies shed light on our understanding of basic molecular and cellular pathways that underlie the beneficial roles of posttraumatic hypothermia, yet many questions still need to be answered, including the roles of posttranscriptional regulation. Both cell cultures and animal model studies have demonstrated the effects of many miRNA species under hypothermic versus normothermic conditions [ 150 , 151 ]. For example, a study of the role of temperature change in dealing with traumatic brain injury (TBI) showed that lower levels of miR-874 under hypothermic conditions could promote cell function by upregulating the levels of essential proteins for normal cell function (e.g., cytosolic or membrane proteins), suggesting role of cooling temperatures in inducing miRNA expression during TBI [ 150 ].…”
Section: Microrna Biology From Extreme Animal Survivalists To Human Health and Diseasementioning
confidence: 99%
“…elegans showed elevated levels of miR-21 in kidney, muscle and spleen and this also correlated with apaf1 , casp3 and casp7 regulation, suggesting a similar role in mediating an anti-apoptosis response under anoxia exposure [ 162 , 163 ]. Another study using a hypothermic rat model showed activation of miR-374-5p in skeletal muscle in response to hypothermia (12 °C), and inducing suppression of Mex3B (muscle excess 3) that ultimately affects genes involved in the apoptosis cascade [ 151 ]. Overall, these studies highlight the roles of temperature and stress specific miRNAs in activating different regulatory pathways and mediating positive metabolic consequences similar to the effects of therapeutic hypothermia after traumatic injury and may provide a guide to comprehend temperature/stress specific miRNA regulation involved in these basic cellular mechanisms.…”
Section: Microrna Biology From Extreme Animal Survivalists To Human Health and Diseasementioning
confidence: 99%